System design and modeling of energy efficient liquid desiccant regeneration system at vacuum condition - Yon, Hao Ren (2018)
Liquid Desiccant Dehumidification System (LDDS) has been one of the attractive alternatives to replace the conventional mechanical dehumidification system in building air conditioning system due to its higher energy efficiency. LDDS is able to shift the electrical energy towards renewable or low-grade energy and can improve indoor air quality with better humidity control. However, the conventional adiabatic packed-bed regenerator requires higher regeneration temperature which of 60-80oC to regenerate higher desiccant solution concentration. This limits the use of the low-grade ore renewable energy as the heat source in the regeneration system of LDDS. Therefore, a novel Absorption-based Liquid Desiccant Regeneration (ALDR) system which operates under vacuum condition is proposed in this work. A prediction model is first developed to predict the system regeneration performance. Several performance indices which are the Moisture Removal Rate (MRR) and Mass Fraction Increase (MFI) are introduced to represent the regeneration performance of the ALDR system. The prediction model is developed based on the energy and mass balance equations and concept of perfectness. The prediction model is then verified with the experimental data. The experimental results are in good agreement with the predicted results with 94.12% of the points within ±10% deviation and the average deviation is less than 3.37%. The developed prediction model is also used to predict the system regeneration performance under varied operating conditions. An effective model is developed to simulate the dynamics of the ALDR system. The dynamic model is developed based on internal and external enthalpy balances and mass balances in the various components and it accounts for dynamic behavior due to the heat and mass transfer processes in the components. This approach is simpler as a detailed enthalpy at each state point can be avoided. The developed dynamic model is verified using the data obtained from the experimental platform built in the laboratory. The dynamic response of the simulation results agrees well with the experimental data. This model is able to predict the relevant parameters such as the temperature, concentration and mass flow of the desiccant solution and also temperatures of the heating and cooling sources when a step change of inlet water temperature is applied to the system. The developed model is useful for designing a controller to control the vacuum pressure in the system so as to achieve the control objective of increasing the regeneration performance of the system. The developed dynamic model can also be adapted to other similar design of regeneration system operating under vacuum condition if the system design data are available. In the research work, the feasibility of the proposed desiccant regeneration system operating under vacuum condition is of the main concern. Therefore, the system regeneration performance and the regeneration temperature should be determined to validate its feasibility and compared with other existing desiccant regeneration systems. The ALDR system is first designed and built in the laboratory. A Singapore patent application of the proposed ALDR system has been filed. From the experimental results obtained, the regeneration temperature of the ALDR system is found to be around 20-35oC when the operating pressure is between 1000Pa and 2000Pa. This is significantly less than that of the existing desiccant regeneration system which is required to be around 60-80oC. The reduction of regeneration temperature allows the potential use of low-grade or renewable energy source in the regeneration system. The power consumption of the proposed ALDR system is also found to have decreased by 40.66% when compared to conventional liquid desiccant regeneration system which validates its energy saving potential. The reduction of regeneration temperature and power consumption of the proposed ALDR system underlines the main contribution of this work.